Business licensing and one stop shops in Indonesia - Steer, Liesbet (The Asia Foundation, 2006)
In 2001, Indonesia embarked on a decentralization process that has had a dramatic impact on the local political landscape, especially in relation to taxation and administrative processes. Rules and procedures that govern licensing, registration, some taxes and user charges have largely been devolved to local governments. A significant number of new licenses and charges have been created at the local level, and most licenses are issued through a complicated system of procedures and agencies. Licensing has become one of the most important barriers to business formalization and growth in Indonesia. The local licensing framework in Indonesia has three key problems, raising transactions costs and inefficiencies. Licensing reform through One Stop Shops (OSS). The Asia Foundation OSS technical assistance program. The methodology has proven to be highly effective.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; decentralization / descentralização

PPFD/PRODER Joint Review and Strategy Proposal for the National PPFD Program Architecture - Final report - Ministry of Planning and Development - Mozambique (MÉTIER, Consultoria e Desenvolvimento, Lda, 2006)
The present report integrates the main conclusions of the three PPFD projects evaluation: PPFDNorth, PPFD-Centre and PRODER, establishing the articulation with the evolution of the political and administrative evolution and relevant for the decentralization process. Based on this analysis the report proposes the architecture of a single National PPFD Program and its main components. This report is based on the main conclusions of an extensive field work covering various provinces and districts and of the various workshops with participation of representatives of the Government at different levels, of the partners and national and international staff from the projects. It constitutes an important basis for the work of the commissions created to start the program formulations. This final report is complemented by other four partial reports: Evaluation report of the PPFD North; Evaluation report of the PPFD Centre; Evaluation report of the PRODER; and Phases 2 and 3 Report: Strategy for a single national PPFD
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; M - evaluation / avaliação; government policy / politica governamental